2012
DOI: 10.1002/bit.24733
|View full text |Cite
|
Sign up to set email alerts
|

In vivo cleavage of transgene donors promotes nuclease‐mediated targeted integration

Abstract: Targeted DNA integration is commonly used to eliminate position effects on transgene expression. Integration can be targeted to specific sites in the genome via both homology-based and homology-independent processes. Both pathways start the integration process with a site-specific break in the chromosome, typically from a zinc-finger nuclease (ZFN). We previously described an efficient homology-independent targeted integration technique that captures short (<100 bp) pieces of DNA at chromosomal breaks created … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
157
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(163 citation statements)
references
References 18 publications
2
157
0
Order By: Relevance
“…In fact no integration of a surrogate reporter plasmid bringing a ZFN site identical to the one in the genome was observed in a recent study (Kim et al 2011). While our manuscript was under revision, Cristea et al (2012) reported that introducing a ZFN site in a donor plasmid could promote its integration into the ZFN targeting site in the genome. Because the same ZFN sites were used in donor plasmids, only a minority of genomic insertions had precise 59 and 39 junctions, presumably due to repetitive digestions by ZFNs (Cristea et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact no integration of a surrogate reporter plasmid bringing a ZFN site identical to the one in the genome was observed in a recent study (Kim et al 2011). While our manuscript was under revision, Cristea et al (2012) reported that introducing a ZFN site in a donor plasmid could promote its integration into the ZFN targeting site in the genome. Because the same ZFN sites were used in donor plasmids, only a minority of genomic insertions had precise 59 and 39 junctions, presumably due to repetitive digestions by ZFNs (Cristea et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…While our manuscript was under revision, Cristea et al (2012) reported that introducing a ZFN site in a donor plasmid could promote its integration into the ZFN targeting site in the genome. Because the same ZFN sites were used in donor plasmids, only a minority of genomic insertions had precise 59 and 39 junctions, presumably due to repetitive digestions by ZFNs (Cristea et al 2012). Interestingly, they found that inefficient donor integration could also happen when the ZFNs used for donor linearization and chromosomal cleavage were not identical.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it should be possible to capture two different ssODNs simultaneously at different positions on the same chromosome (e.g., for the introduction of two loxP sites flanking a set of exons) depending on the efficiency of this process. Furthermore, combination of the segmental deletions with the application of ssODNs (Chen et al 2011;Bedell et al 2012) or the introduction of nuclease-stimulated ligation of an exogenous donor DNA (Cristea et al 2013;Maresca et al 2013) could facilitate the targeted replacement of a desired genomic segment with a specific sequence variant for a more complete deconvolution of function.…”
Section: Chromosomal Deletions and Inversions In Zebrafishmentioning
confidence: 99%
“…Since artificial nuclease systems such as ZFNs produce the sticky ends, these overhangs were used as the tabs for sticking, by simply adding the overhangs to the knock-in cassette or the target site of ZFNs to the donor plasmid (Orlando et al 2010;Cristea et al 2013). This system was subsequently refined as the ObLiGaRe method, which enabled obligate ligation by switching the left and right target sites of ZFNs and TALENs added in the plasmid donor and utilizing the obligate heterodimeric nucleases (Maresca et al 2013).…”
Section: Nhej-mediated Gene Knock-inmentioning
confidence: 99%